Clinical Research in Hepatology in the COVID‐19 Pandemic and Post‐Pandemic Era: Challenges and the Need for Innovation. Issue 5 (6th November 2020) - Verna, Elizabeth C.; Serper, Marina; Chu, Jaime; Corey, Kathleen; Fix, Oren K.; Hoyt, Karen; Page, Kimberly A.; Loomba, Rohit; Li, Ming; Everson, Gregory T.; Fried, Michael W.; Garcia‐Tsao, Guadalupe; et al.
Abstract : The severe acute respiratory syndrome coronavirus 2 pandemic has drastically altered all facets of clinical care and research. Clinical research in hepatology has had a rich tradition in several domains, including the discovery and therapeutic development for diseases such as hepatitis B and C and studying the natural history of many forms of chronic liver disease. National Institutes of Health, foundation, and industry funding have provided important opportunities to advance the academic careers of young investigators while they strived to make contributions to the field. Instantaneously, however, all nonessential research activities were halted when the pandemic started, forcing those involved in clinical research to rethink their research strategy, including a shift to coronavirus disease 2019 research while endeavoring to maintain their preexisting agenda. Strategies to maintain the integrity of ongoing studies, including patient follow‐up, safety assessments, and continuation of investigational products, have included a shift to telemedicine, remote safety laboratory monitoring, and shipping of investigational products to study subjects. As a revamp of research is being planned, unique issues that face the research community include maintenance of infrastructure, funding, completion of studies in the predetermined time frame, and the need to reprogram career path timelines. Real‐world databases, biomarker and long‐term follow up studies, and research involving special groups (children, the homeless, and other marginalized populations) are likely to face unique challenges. The implementation of telemedicine has been dramatically accelerated and will serve as a backbone for the future of clinical research. As we move forward, innovation in clinical trial design will be essential for conducting optimized clinical research.